Pengaruh Kecerdasan Emosional, Spiritual Dan Sosial Mahasiswa Akuntansi Terhadap Pemahaman Akuntansi - Aritonang, Sri Lestari; Poniman, Poniman (Peneliti.net, 2023)
Student success is not only influenced by emotional, spiritual intelligence but also greatly influenced by other intelligences, namely student social intelligence. The purpose of this study was to determine the influence of emotional, spiritual, and social intelligence on the understanding of accounting students. This study uses a quantitative approach which is a research method based on the philosophy of positivism used in certain populations and samples using surveys and questionnaire instruments. The respondents in this study are students majoring in accounting in Batam City and who have been registered on the DIKTI (Directorate General of Higher Education) website for the odd period learning year 2022 with a total of 22,589 students. The results of the study as evidenced by the F test show that the calculated F value of 53.615 is greater than the F table which is 2.70 with a significance level of 0.000 smaller than 0.05 so that it can be concluded that the emotional, spiritual, and social intelligence of accounting students silmultan affects the understanding of accounting. However, based on partial analysis emotional intelligence affects the understanding of accounting. While spiritual has no effect on the understanding of accounting. And Social accounting students influence the understanding of accounting.